163k views
0 votes
How many solutions does 5x - 1 = 10x - 4 - 5x + 3 have?

User Medrod
by
5.0k points

1 Answer

4 votes

Answer:

Explanation:

Simplifying

5x + -1 = 10x + -4 + -5x + 3

Reorder the terms:

-1 + 5x = 10x + -4 + -5x + 3

Reorder the terms:

-1 + 5x = -4 + 3 + 10x + -5x

Combine like terms: -4 + 3 = -1

-1 + 5x = -1 + 10x + -5x

Combine like terms: 10x + -5x = 5x

-1 + 5x = -1 + 5x

Add '1' to each side of the equation.

-1 + 1 + 5x = -1 + 1 + 5x

Combine like terms: -1 + 1 = 0

0 + 5x = -1 + 1 + 5x

5x = -1 + 1 + 5x

Combine like terms: -1 + 1 = 0

5x = 0 + 5x

5x = 5x

Add '-5x' to each side of the equation.

5x + -5x = 5x + -5x

Combine like terms: 5x + -5x = 0

0 = 5x + -5x

Combine like terms: 5x + -5x = 0

0 = 0

Solving

0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

User Alexis Hassler
by
5.1k points